Metabolismo de defesa em Solanum tuberosum em resposta à fitobactéria Pectobacterium atrosepticum e a indutores de resistência vegetal - Faillace, Giulia Ramos (2015)
The potato is the third most important consumed food in the world. Despite its high productivity, many pest problems cause losses in the quantity and quality of the product. Its high susceptibility to pathogens such as the necrotrophic bacteria Pectobacterium atrosepticum, has led to the indiscriminate use of pesticides, causing damage to the environment and human population. Studies of plant resistance inducers represent an alternative for disease control in some cultures by promoting innate defense system against pathogens. Understanding the changes in plant metabolism related to defense enables the evaluation and development of new strategies and products to disease control. This work aimed was to evaluate some of the mechanisms involved in defense metabolism of Solanum tuberosum in response to the phytobacteria Pectobacterium atrosepticum as well as to the XTH and ASM elicitors.To this end, we analyzed the activities of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APx), enzymes related to defense metabolism, polyphenol oxidase (PPO), peroxidase (POX), phenylalanine ammonia lyase (PAL), and pathogenesis-related proteins, β-1,3-glucanase and chitinase. It was also determined the synthesis of phenolic compounds and salicylic acid (SA), and the assessment of disease progression caused by the phytobacteria in leaves pretreated with XTH. Our results showed that the elicitor XTH was able to delay the disease progression and symptoms caused by the bacteria P. atrosepticum.The elicitors ASM and XTH promoted the activation of the antioxidant enzymes, as well as the induction of certain enzymes related to defense before and after the bacterial inoculation, differing from the response pattern observed in the leaves treated only with P. atrosepticum. In addition, we observed an increase in free SA levels in leaves treated only with the phytobacteria, differing from the other treatments. In conclusion, the elicitor XTH promotes resistance to the necrotrophic bacteria P. atrospeticum by the defense metabolism activation and modulation of S. tuberosum.